High-throughput assays for detection of the F1534C mutation in the voltage-gated sodium channel gene in permethrin-resistant Aedes aegypti and the distribution of this mutation throughout Thailand - Jintana Yanola (2018)
Objectives To develop rapid monitoring tools to detect the F1534C permethrin-resistance mutation in domain IIIS6 of the Aedes aegypti voltage-gated sodium channel gene and determine the frequency and distribution of this mutation in Thailand. Methods A TaqMan SNP genotyping and an allele specific PCR (AS-PCR) assay were developed and validated by comparison with DNA sequencing of homozygous susceptible and homozygous resistant laboratory strains, their reciprocal-cross progenies, and field-caught mosquitoes. To determine the resistance phenotype of wild-caught A. aegypti, mosquitoes were exposed to 0.75% permethrin paper. The AS-PCR assay was used to screen 619 individuals from 20 localities throughout Thailand. Results Overall, both assays gave results consistent with DNA sequencing for laboratory strains of known genotype and for wild-caught A. aegypti. The only slight discrepancy was for the AS-PCR method, which overestimated the mutant allele frequency by 1.8% in wild-caught samples. AS-PCR assays of permethrin-exposed samples show that the mutant C1534 allele is very closely associated with the resistant phenotype. However, 19 permethrin-resistant individuals were homozygous for the wild-type F1534 allele. DNA sequencing revealed all these individuals were homozygous for two other mutations in domain II, V1016G and S989P, which are known to confer resistance (Srisawat 2010). The F1534C mutation is widespread in Thailand with mutant allele frequencies varying among populations from 0.20 to 1.00. Conclusions These assays can be used for the rapid detection of the F1534C resistance mutation in A. aegypti populations. The F1534C, and other, mutations underlie an extremely high prevalence of pyrethroid resistance in Thailand. © 2011 Blackwell Publishing Ltd.